Membrane filtration enrichment and optimization of nucleic acid extraction for qPCR detection of pathogenic bacteria in water - an experiment with Mycobacterium abscessus tester strain - Yan WU; Xiao ZHANG; Liang ZHANG; Fangxiao XING; Lan ZHANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo establish a sensitive, reliable and rapid pre-treatment method for enrichment and nucleic acid extraction of pathogenic bacteria in water for fluorescent quantitative PCR (qPCR) detection of pathogenic bacteria in water. MethodsThe tester strain used in the experiment was Mycobacterium abscessus (American Type Culture Collection [ATCC] 19977) at concentration of 3.10 × 108 colony form unit (CFU)/mL. The nucleic acid of the tester strain was extracted using centrifugal column and magnetic bead extraction kits combined with elutions of different membranes. The nucleic acid extraction conditions were optimized by using beads of different materials, sizes and numbers and the number of homogenization cycles. The extracted nucleic acid was subjected to qPCR assay to compare the extraction efficiency of each method. qPCR was performed on spiked water samples using optimal extraction conditions to examine the whole process recovery and detection limits. ResultsThe highest recovery of 81.03% ± 19.23% and detection limit of 6.20 CFU/100 mL were achieved using the procedures including 0.20 μm membrane filtration, six homogenization cycles with seven large zirconium beads, and TIANMicrobe Magnetic Envir-DNA Kit based extraction. ConclusionUsing homogenizer and TIANMicrobe Magnetic Envir-DNA Kit is more efficient for the enrichment and nucleic acid extraction of pathogenic bacteria in water for qPCR detection.